Effectiveness of psychological interventions for reducing depressive symptomatology and overload and improving quality of life in informal caregivers of non-institutionalized dependent elderly: a systematic review - Barrero-Mejias, Marco Antonio; Gómez-Martínez, Sandra; González-Moreno, Jesús; Rueda-Extremera, María; Izquierdo-Sotorrio, Eva; Cantero García, María (Frontiers in Medicine, 2024)
Introduction The phenomenon of aging is distinguished by profound life transformations, with the most dependent group being constituted by elderly individuals. The responsibility for their care primarily falls on the figure of the informal caregiver. The scarcity of time, the stress associated with caregiving, the financial, work-related, and personal difficulties it entails, make it a collective with high probabilities of experiencing various psychological disorders. Interventions that have shown the best results are those of multiple components, composed of various techniques that seek to adapt to the reality of the informal caregiver. Method The purpose of this study is a systematic review of effective interventions on depressive symptoms, emotional wellbeing, burden, or quality of life in informal caregivers of non-institutionalized dependents from 2018 to the present. A search was conducted in November 2023, on Pubmed, Pubmed Central, Proquest, and Scielo. The final review was conducted on 11 articles. Results The results indicate that multiple component interventions including cognitive behavioral techniques and psychoeducation in combination with stress coping techniques and social support are more effective on depressive symptoms, burden, quality of life, and increasing the social support network. Discussion Results on web-based programs demonstrate their efficacy and effectiveness, but require a greater number of trials to adjust their methodological quality and content to the idiosyncrasies of the informal caregiver.